ESTUDO DAS CONDIÇÕES DE ACESSIBILIDADE DA PRAÇA DO MARCO DA CAPITAL NACIONAL DE LITERATURA DE PASSO FUNDO - Ferrari, Maiara; Rossetto, Lucas A.; Klein, Rodrigo; Oliveira, Cristiano; Tagliari, Rodrigo R. (Salão do Conhecimento, 2013)
Resumo